Elevated MMP-9, Survivin, TGB1 and Downregulated Tissue Inhibitor of TIMP-1, Caspase-3 Activities are Independent of the Low Levels miR-183 in Endometriosis - Muharam R; Bowolaksono A; Maidarti M; Febri RR; Mutia K; Iffanolida PA; Ikhsan M; Sumapraja K; Pratama G; Harzif AK; Hestiantoro A; Wiweko B (Dove Medical Press, 2024)
R Muharam,1- 3 Anom Bowolaksono,1,4 Mila Maidarti,1- 3 Ririn Rahmala Febri,1 Kresna Mutia,1 Pritta Ameilia Iffanolida,1 Muhammad Ikhsan,1- 3 Kanadi Sumapraja,1- 3 Gita Pratama,1- 3 Achmad Kemal Harzif,1- 3 Andon Hestiantoro,1- 3 Budi Wiweko1- 3 1Human Reproduction, Infertility and Family Planning Research Center, Indonesian Medical Education and Research Institute, Faculty of Medicine, Universitas Indonesia Jakarta, Jakarta, 10430, Indonesia; 2Division of Reproductive Endocrinology and Infertility Department of Obstetrics and Gynecology, Faculty of Medicine Universitas Indonesia, DKI Jakarta, 10430, Indonesia; 3Yasmin IVF Clinic, Dr. Cipto Mangunkusumo General Hospital, Jakarta, 10430, Indonesia; 4Cellular and Molecular Mechanisms in Biological System (CEMBIOS) Research Group, Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Indonesia, Depok, 16424, IndonesiaCorrespondence: R Muharam, Division of Reproductive Endocrinology and Infertility, Department of Obstetrics and Gynecology - Faculty of Medicine Universitas Indonesia, Jl. Diponegoro No. 71, Salemba, Jakarta Pusat, DKI Jakarta, 10430, Indonesia, Tel +62 3928720 / +62 816 1188027, Email rmuharam@yahoo.comPurpose: This study aimed to measure the correlation between miR-183 and gene expression that regulates apoptosis and adhesion mechanism that may be linked to the pathogenesis of endometriosis.Patients and Methods: Forty-four subjects, including 22 control subjects, participated in this study. We collected ectopic endometriosis and endometrial samples. For the control, the sample was taken from endometrial tissue through pipelle biopsy. RNA was extracted from all tissues using RNA mini kit, and the expression was assessed using quantitative-real time PCR. Relative mRNA and miRNA expression were presented using the formula of the Livak method. The data were statistically analyzed using GraphPad Prism 8.Results: The expression of Caspase-3, Survivin, Integrin β 1 (ITGB1), matrix metalloproteinase-9 (MMP-9), and tissue inhibitor of matrix metalloproteinase-1 (TIMP-1) (adhesion- and apoptosis-related gene) were calculated using the relative expression method. We found significant differences in Caspase-3, Survivin, ITGB1, MMP-9, and TIMP-1 expression between ectopic endometriosis tissues of women with endometriosis compared to healthy endometrium. MMP-9, Survivin, and ITGB1 was significantly increased in the endometriosis group, while Caspase-3, TIMP-1, and miR-183 were significantly reduced in the endometriosis group. No correlation was found between the expression level of miR-183 and Caspase3, Survivin, ITGB1, and Cadherin in both tissue types.Conclusion: Despite the difference in expression levels of miR-183 and associated adhesion- and apoptosis-related genes, there was no significant association between miR-183 with specific adhesion and apoptosis genes in endometriosis tissue.Keywords: endometriosis, miR-183, MMP-9, TIMP1, apoptosis, antiapoptosis